The effect of adenoidectomy on pulmonary function in children: prospective controlled study - Yagız Agayarov, Ozlem; Aliyeva, Aynur; Kocahan, Sayad (The European Research Journal, 2023)
Objectives: Adenotonsillar hypertrophy (AH) is a prevalent condition in children that can cause significant complications if left untreated. In this study, we investigated the impact of adenoidectomy on pulmonary function tests (PFTs) and explored the relationship between spirometric parameters in affected children. By evaluating these factors, we can better understand the post-surgical outcomes and the potential benefits of surgical intervention. Methods: The present study utilized a prospective controlled design to conduct a before and after clinical trial involving 23 children diagnosed with upper airway obstruction resulting from AH. Five specific spirometric parameters were selected to evaluate pulmonary function before and 1-3 months following the adenoidectomy procedure. Additionally, adenoid grade scores and gender differences were recorded for each patient to assess their effect on the lung. Results: Peak expiratory flow (PEF) (p = 0.002), the first second of expiration (FEV1) (p < 0.001), and the ratio of FEV1/FVC (p = 0.001) significantly increased postoperatively. However, no significant correlations were found between the forced vital capacity (FVC) (p = 0.39) and mid-expiratory forced expiratory flow (FEF25-75) (p = 0.2). Rising of the FVC, PEF, FEV1, and FEV1/FVC was observed in AH grade III patients compared to AH grade IV patients following the surgical intervention, in comparison to the preoperative baseline, especially statistical significance was FEV (p = 0.047), indicating a noteworthy change in lung function. Conclusions: These findings emphasize the beneficial effects of adenoidectomy on PFTs and highlight that adenoidectomy positively affects the upper and lower airways.